Graphene hybrids: synthesis strategies and applications in sensors and sensitized solar cells - Badhulika, Sushmee; Terse-Thakoor, Trupti; Chaves Villarreal, Claudia M.; Mulchandani, Ashok (Frontiers in Chemistry, 2015)
Graphene exhibits unique 2-D structural, chemical and electronic properties that lead to its many potential applications. In order to expand the scope of its usage, graphene hybrids which combine the synergetic properties of graphene along with metals/ metal oxides and other nanostructured materials have been synthesized and are a widely emerging field of research. This review presents an overview of the recent progress made in the field of graphene hybrid architectures with a focus on the synthesis of graphene-carbon nanotube (G-CNT), graphene-semiconductor nanomaterial (G-SNM) and graphene-metal nanomaterial (G-MNM) hybrids. It attempts to identify the bottlenecks involved and outlines future directions for development and comprehensively summarizes their applications in the field of sensing and sensitized solar cells.